Population dinamics of Acroptilon repens L. and weed community structure post flooding - Gajardo, Omar Ariel; Avilés, Lucrecia María; Cañón, Silvia (Ecosistemas y Recursos Agropecuarios, 2020)
Acroptilon repens is a perennial invasive weed that significantly reduces agricultural production. In irrigated production systems, its control is proposed by flooding the soil for short periods. However, the behavior of the population and the community after flooding is unknown. For this reason, in this work we analyze the population dynamics of A. repens and the structure of the species community after a short period of flooding. For this, assay was conducted in a lot infested by A. repens (63 ramets m−2) that was flooded for: 0, 10 and 20 days. After water supply suspension, the behavior of the population of the species was evaluated, determining the dry matter present by phenological stage: bloom, pre-bloom and rosette from seed or rhizome, as well as of the underground struc- tures of the first 20 cm. The coverage of the other species present was established according to the Brawn Blanquet scale. It was observed that the population flooded for 10 days recovered from the regrowth from the remaining rhizomes and, where the flood was maintained for 20 days, the recruitment of new plants from seeds was observed. The weed community also changed, with an increase in the diversity index observed 75 days after the flood was suspended.